Unlocking the recipe for organizational resilience: A review and future research directions - Su, Wenjia; Junge, Sebastian (European management journal, 2023)
In these challenging times of climate change, pandemic, and war, research on organizational resilience has gained significant momentum. The purpose of our review is to examine how adverse events and antecedents at the individual, group, organizational, and network levels affect organizational-resilience processes and their outcomes. Based on a systematic search in 53 top-ranked journals over a period of 25 years from 1997 to 2022 and an additional backward reference search, we conduct a framework-based literature review of 127 publications. We find that the form of the adverse event (i.e., its emergence, novelty, and severity) determines the resilience process and underlying actions. To address the multilevel facets of organizational resilience, we integrate a comprehensive array of antecedents at the individual, group, organizational, and network levels, and show that their influence on resilience processes and outcomes can be beneficial or detrimental depending on the context. We highlight research opportunities along our framework (antecedents, process, and outcomes) and derive a set of propositions.